2015
DOI: 10.1039/c5nj00256g
|View full text |Cite
|
Sign up to set email alerts
|

Fluorosolvatochromism of furanyl- and thiophenyl-substituted acetophenones

Abstract: Fluorosolvatochromism of four furanyl- or thiophenyl-substituted acetophenone derivatives is suitable to measure environmental effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…In all cases, the plots of the solvent parameters versus the emission energy do not disclose an obvious relationship. This behavior is in agreement with that of other donor–acceptor biaryl-type dyes, such as for example para -hetaryl-substituted benzophenone derivatives, whose emission properties were demonstrated to depend on a complex interplay of different solvent parameters [ 38 ]. Unfortunately, the limited solubility of the derivatives 6b – e did not permit to employ a large series of solvents that is required for such a multiparameter analysis of these compounds.…”
Section: Discussionsupporting
confidence: 87%
“…In all cases, the plots of the solvent parameters versus the emission energy do not disclose an obvious relationship. This behavior is in agreement with that of other donor–acceptor biaryl-type dyes, such as for example para -hetaryl-substituted benzophenone derivatives, whose emission properties were demonstrated to depend on a complex interplay of different solvent parameters [ 38 ]. Unfortunately, the limited solubility of the derivatives 6b – e did not permit to employ a large series of solvents that is required for such a multiparameter analysis of these compounds.…”
Section: Discussionsupporting
confidence: 87%
“…These compounds exhibited strong uorosolvatochromism, as a result of the substantial photoinduced ICT process. Another study using thiophene ring as electron donating group for thiophenylsubstituted acetophenone was given by Friebe et al; 17 where the uorescence emission spectra were found to depend on the nature of the solvent, and the uorosolvatochromism were observed in wide range of solvents of different acidity, basicity and polarity. It is well known that 2,5-thienylene derivatives exhibit less extended emission solvatochromic range than 1,4phenylene analogues even if the ICT is more important in the rst case.…”
mentioning
confidence: 99%
“…To understand the contribution of different aspects of solute‐solvent intermolecular interactions, spectral shift of this chromophoric dye observed in 20 different pure solvents is correlated with solvent property parameters using linear solvation energy relationship (LSER) multiparametric approaches . Two most widely employed LSER i. e. Kamlet‐Taft and Catalan equations, which considers solvent properties such as, HBD acidity, HBA basicity, dipolarity and polarizability have been used in the present study . To study the major contribution from any other solvent polarity parameters such as dipole moment, dielectric constant, electron pair donor/acceptor capabilities, hydrophobicity/hydrophilicity etc.…”
Section: Introductionmentioning
confidence: 99%